The identity of Synotis borii (Asteraceae-Senecioneae) - Xu, Ying; Singh, Harsh; Tang, Ming (Phytotaxa, 2023)
Our critical examination of ample material including the type specimen and our study of the protologue convinced us that Synotis borii is not different from S. saluenensis and therefore should be synonymized with the latter.